Answer:
Step-by-step explanation:
We first need to define a couple of variables. Let s = the cost of 1 squash and z = the cost of 1 zucchini.
Now lets translate the words into algebra:
"The cost of 5 squash and 2 zucchini is $1.32" ===> 5s + 2z = 1.32
"Three squash and 1 zucchini cost $0.75" ===> 3s + z = 0.75
There are several ways to solve systems of equations. Let's use substitution. We can find what z equals in terms of s by manipulating the second equation:
3s + z = 0.75
-3s -3s
------------ -------------
z = -3s +0.75
Now lets substitute (-3s + 0.75) into the first equation for z, then solve for s:
5s + 2(-3s + 0.75) = 1.32
Can you handle it from here?
(Hint: Once you have solved for s, you can substitute that value back into either of the equations and solve for z.)
Answer:
f(x) + g(x) = x^2 + 4x + 35
Step-by-step explanation:
Add like terms from f(x) and g(x):
f(x) + g(x) = x^2 + 3x + 28 + x + 7, or
f(x) + g(x) = x^2 + 4x + 35
Answer:
The Answer above The Image
Step-by-step explanation:
Thanks…………………
18 - 2[x + (x-5)]
First I would get rid of the inside parenthesis by distributing the + to everything inside and end up with;
18 - 2[x + x - 5]
Then I'd combine like terms inside the brackets
18 - 2[2x - 5]
Then I'd multiply what is inside the brackets by the -2
18 - 4x + 10
I'd combine like terms and end up with:
28 - 4x......or rewritten as -4x + 28
Jdurjrjufurjrjrjrurrurjrn it is 6